Disseminated cryptococcosis presenting as mediastinal and hilar lymphadenopathy in an immunocompetent patient. Issue 4 (26th May 2016) - Murakami, Yasushi; Oki, Masahide; Saka, Hideo; Kajikawa, Shigehisa; Murakami, Ayuka; Ishida, Akane
Abstract: We herein report a rare case of disseminated cryptococcosis presenting as mediastinal and hilar lymphadenopathy in a young immunocompetent man. A previously healthy 26‐year‐old man presented with persistent headache and nonproductive cough. Chest computed tomography indicated mediastinal and hilar lymphadenopathy. Cryptococcal lymphadenitis and meningitis was confirmed by endobronchial ultrasound‐guided transbronchial needle aspiration and central spinal fluid examination, respectively. He received liposomal amphotericin B and flucytosine followed by fluconazole and finally improved. Abstract : We encountered a rare case of disseminated cryptococcosis presenting as hilar and mediastinal lymphadenopathy in a young immunocompetent man. Chest X‐Ray showed massive lymphadenopathy mimicking thoracic malignancies.